Effect of Local Gentamicin Infiltration on Surgical Site Infection Following Lower Limb Open Reduction and Internal Fixation: A Randomized Double-Blinded Trial - BUHARI ZAILANI; ALABI IBRAHIM; Okor Nduibisi; SHAPHAT SHUAIBU IBRAHIM; EMUAN TIMOTHY; UMAR MUHAMMED; STEPHEN YUSUF; BUKAR SHEHU; ARIF SAFIYAN LABBO (West African Journal of Allied Health Sciences, 2026)
Background: Surgical site infection (SSI) remains a formidable complication in orthopedicsurgery, particularly in the presence of implanted biomaterials such as plates and intramedullarynails. While perioperative antimicrobial prophylaxis is standard practice, local antibioticinfiltration may offer additional protection against infection in open reduction and internalfixation procedures.Objective: To evaluate the additive effect of local gentamicin infiltration on the incidence ofsurgical site infection following lower limb open reduction and osteosynthesis.Methods: This prospective, randomized, double-blind, hospital-based interventional studyenrolled 100 patients indicated for open plating or intramedullary nailing of lower limb fracturesor deformities. Participants were randomized into two groups of 50 each: Group A (control)received 4 mL of normal saline, and Group B (intervention) received 160 mg gentamicin (4 mL)infiltrated into the surgical wound prior to closure. Both groups received intravenous ceftriaxoneprophylaxis intraoperative and for 72 hours postoperatively. Wounds were drained, and patientswere followed for 90 days. Wound assessment for infection was performed on days 3, 7, 10, 14,28, and at 6 and 12 weeks using the ASEPSIS score.Results: Ninety-three patients completed 90-day follow-up (7 lost to follow-up). The majoritywere male (74.2%) and aged 26–35 years (37.6%). Traumatic fracture fixation comprised 83.9%of cases, with femur (47.7%) and tibia (36.6%) as the most common anatomical sites. Platingwas the predominant fixation method (50.5%). The overall infection rate was 11.8%, with 17.4%in Group A and 6.4% in Group B; however, the difference was not statistically significant (p =0.120). Significant risk factors for SSI included BMI >25 kg/m² (p = 0.010), operative duration>3 hours (p = 0.019), and perioperative blood transfusion (p = 0.001). No association was foundwith diabetes, hypertension, or ASA class II status. Staphylococcus aureus was the mostfrequently isolated organism.Conclusion: Local gentamicin infiltration was associated with a lower infection rate comparedwith placebo, though the difference did not reach statistical significance. Identified modifiablerisk factors—obesity, prolonged operative time, and blood transfusion—warrant targetedpreventive strategies.